Odpowiedź :
Odpowiedź:
1 i 5/7 + 2 i 2/7 = 3 i 7/7 = 4
3 i 5/9 - 8/9 = 2 i 14/9 - 8/9 = 2 i 6/9 = 2 i 2/3
3/4 * 1 i 1/4 = 3/4 * 5/4 = 15/16
9/17 : 3/17 = 9/17 * 17/3 = 3 skracamy 17 i 17 przez 17 a 9 i 3 przez 3
[tex]a) \ 1\dfrac{5}{7}+2\dfrac{2}{7} = 3\dfrac{7}{7} = 4\\\\\\b) \ 3\dfrac{5}{9}-\dfrac{8}{9} = 2\dfrac{14}{9}-\dfrac {8}{9} =2\dfrac{6}{9} = 2\dfrac{2}{3}\\\\\\c) \ \dfrac{3}{4}\cdot1\dfrac{1}{4} = \dfrac{3}{4}\cdot\dfrac{5}{4} = \dfrac{15}{16}\\\\\\d) \ \dfrac{9}{17}:\dfrac{3}{17} = \dfrac{9}{17}\cdot\dfrac{17}{3} =\dfrac{9}{3} = 3[/tex]